Taxezopidine-G from needles and young stems of Taxus baccata L. growing in Iran - M Pirali-Hamedani; Verdian Rizi MR; SH Rezazadeh; R Dowlatabadi; A Hadjiakhoondi; M Amini; D Yazdani (Institue of Medicinal Plants, ACECR, 2005)
Background: Taxus species are important due to their content of Taxol, baccatin III, 10- deacetyl baccatin and other taxoids suitable to change to active pharmaceutical ingredients, which are used as anti-neoplastic agents. Investigations on taxoids carried out during the past four decades, resulted in identification of more than 350 taxoids. Objective: This study aimed to isolate and identify taxoids of Taxus baccata endogenous to the north of Iran. Method: Removing of fats, extraction of components with an organic solvent and then separation and purification of components with silica gel based column chromatography was done. Identification was carried out using NMR spectra of components. Results: Taxezopidine-G was separated and identified. Conclusion: Taxezopidine-G in Taxus baccata was isolated which had not been repoted in this spcies, previously.